The Place and Importance of Propolis in Cancer Immunotherapy - Nigahban İPEK; Berna PINARBAŞI; Ayşe GÜNEŞ BAYIR (Bezmiâlem Science, 2022)

(untitled)
Nowadays, the increasing number of cancer patients is a major concern all over the world. Therefore, finding safe and effective treatments has become one of the main goals of researchers. Immunotherapy is a form of treatment that allows the individual to fight against many diseases including cancer by using the immune system. The aim is to enable cells of the immune system to target and destroy cancer cells. Immunotherapeutic strategies in cancer are spread to a wide range of research areas including monoclonal antibodies, cancer vaccines, adoptive immunotherapy, cytokines, and immune system enhancing drugs. Due to the specificity of the immune response in new treatment methods, it is aimed that the immunity against the tumor is to destroy the tumor selectively without harming the patient. In recent scientific studies, it has been revealed that propolis is one of the most promising immunomodulating agents. Propolis is a natural medicine that widely used since ancient times and contains several bioactive compounds. More than 300 components of propolis have been identified to date and in vitro, in vivo and clinical studies of these components are ongoing. The major anticancer components in propolis are Convective available potential energy, chrysin, nemorosone, artepilin C, galangin and cardanol. The in vitro, in vivo and human clinical researches report that the propolis shows positive effect against the several different cancer types. Propolis as a natural food with these properties may support the immune system and body function of cancer patients.